Toxicological assessment of anthropogenic Gadolinium in seawater: biochemical effects in mussels Mytilus galloprovincialis - Henriques, Bruno (2020)
Recently, anthropogenic enrichment of rare earth elements (REE) have been reported in natural environments, due to increasing use and discharges of hospital/industrial wastewaters. Gadolinium (Gd), which is mainly used as contrast agent for magnetic resonance imaging in medical exams, may reach concentrations in water up to two orders of magnitude larger than baseline levels. Nevertheless, in marine systems scarce information is available concerning the toxicity of REE towards inhabiting organisms. This study aimed to evaluate the biochemical impact of anthropogenic Gd in the Mediterranean mussel Mytilus galloprovincialis, which is a species of commercial interest and one of the most accepted pollution bioindicator. Organisms were exposed to different concentrations of Gd (0, 15, 30, 60, 120 µg/L) for 28 days. At the end of the experiments, biomarkers related to mussels’ metabolic (electron transport system activity and energy reserves content), oxidative stress status (cellular damage and the activity of antioxidant and biotransformation enzymes) and neurotoxic effects (activity of the enzyme Acetylcholinesterase) were measured, as well as Gd bioconcentration in organisms. Results showed a high content of Gd (2.5±0.50 µg/g) in mussels exposed to the highest concentration, contrary to those at control condition and at 15 and 30 μg/L of Gd (levels below 0.38 µg/g). Although no mortality was observed during the experimental period, exposure to Gd strongly affected the biochemical performance of M. galloprovincialis, including the decrease on mussels’ metabolism, induction of oxidative stress and neurotoxicity, particularly evidenced at intermediate concentrations. These results may indicate that up to certain stressful levels, although lowering their metabolism, organisms may be able to activate defense strategies to avoid cellular injuries which, on the other hand, may compromise mussels physiological performance such as growth and reproduction success. Nevertheless, our findings support that the widespread utilization of Gd may represent an environmental risk in the future.